Cytotoxic action of the leaves of Uvaria chamae P.Beauv. and Dicliptera paniculata (Forssk.) I.Darbysh. from Nigeria mediated through intrinsic apoptotic pathway induction in four cancer cell lines - Godwin E. Asenye; Toluwanimi E. Akinleye; Uwem E. George; Bob I. Mgbeje; Olubusuyi M. Adewumi; Johnson A. Adeniji; Omonike O. Ogbole; Patrick E. Ebong (Elsevier, 2023)
Background: Over the years, the morbidity and mortality due to cancer have continued to increase worldwide. Plants are well utilized in Nigeria ethno-medicine for cancer treatment. However, scientific evidence, particularly at the molecular level, has been lacking, and biodiversity loss is a threat. Aim of the study: The cytotoxic activity of the leaves of six plants used in Nigeria ethno-medicine was investigated and the molecular pathway of cytotoxic action of two active extracts on four cancer cell lines (A549, RD, MCF-7, and HeLa) was also assessed. Materials and methods: Cytotoxic activities of the plant extracts were assessed on breast (MCF-7), lung (A549), cervical (HeLa), adenocarcinoma and rhabdomyosarcoma (RD) cells using MTT cell viability assay in a time-dependent manner. The sandwich ELISA method was used to assess the protein expressions (Bcl-2, BAX, and executioner caspase 3) involved in the apoptotic pathway in cancer cells after treatment with cytotoxic extracts. UHPLC-MS/MS approach was used to analyze the possible bioactive phytochemicals of the cytotoxic plant extract. Results: Uvaria chamae and Dicliptera paniculata extracts displayed good cytotoxicity across all cell lines in a time- and concentration-dependent manner (CC50 <30 µg/mL). Increased pro-apoptotic BAX and lowered expression of anti-apoptotic Bcl-2 show the cytotoxic action of the two extracts followed the intrinsic apoptotic pathway compared to untreated cells. The increased expression of executioner caspase 3 indicated that the intrinsic apoptotic pathway was caspase-dependent. Conclusion: The anticancer potential of U. chamae and D. paniculata in this study validates the use of these plants in Nigerian ethno-medicine, highlighting apoptosis as a molecular pathway of their cytotoxicity.